Access to Health Services Affects the Level of Adherence to Taking Medication for Hypertensive Patients At Puskesmas Medan Area Selatan Year 2024 - dinillah, Izzah; Siregar, Pinta Pudiyanti (Buletin Farmatera, 2024)
Abstract: Hypertension is known as a silent disease. Compliance of patients with hypertension is essential because hypertension must always be controlled. Access to healthcare is one of the reasons for this non-compliance. This study aims to determine the influence of access to health services on the level of medication adherence of hypertensive patients in Puskesmas Medan Area Selatan. This type of research is descriptive analytics with a cross-sectional design. The research subjects used were 98 hypertension patients in Puskesmas Medan Area Selatan who met the inclusion and exclusion criteria. Sampling is based on purposive sampling and is carried out by Chi-Square Test. The results of the Chi-Square Test obtained a value of P value = 0.001 (P0.05) which means that access to health services has a significant influence on the level of medication adherence of hypertension patients in Puskesmas Medan Area Selatan. Access to health services has a significant influence on the level of medication adherence in hypertensive patients, where the easier it is to access health services, the more compliant patients will be to take medication.